ผลของกระบวนการลดพฤติกรรมสุขภาพที่ไม่เหมาะสมและเพิ่มต้นทุนชีวิตของเยาวชน โดยการมีส่วนร่วมของชุมชน - สุขวัจนี (Arissara Sukwatjanee) อริสรา (Journal of Behavioral Science for Development, 2016)
(Effectiveness of a Process to Decrease Inappropriate Health Behaviors and Increase Life Cost of Young Adults through Community Participation) Abstract The purposes of this study were to explore: 1) inappropriate health behaviors and life cost situations among young adults and 2) effectiveness of a process to decrease inappropriate health behaviors and increase life cost for young adults through community participation. Action Research with an integration of both qualitative and quantitative approaches was designed for the study. 484 participants were purposively recruited from students of high school grade 1-6 living in Phra Nakhon Si Ayutthaya Province to participate in 6 projects: 1) safety driving; 2) safety sex; 3) antidrug addict; 4) family model; 5) devoted mind; and, 6) football team; established to decrease inappropriate health behaviors and increase and life cost among participants for 6 months. Quantitative data assessing the participant’s inappropriate health behaviors and life cost levels were analyzed by mean different statistics. Qualitative data from interviewing, focus group discussion, observation, and field notes were analyzed by content analysis. The results revealed that after 6-month study participation, the participants reported significantly decreased inappropriate health behavior level while their life asset level significantly increased at p <. 05. The inappropriate health behaviors among participants were: 1) no exercising; 2) drinking; 3) unsafe sex; 4) violence; 5) no helmet; 6) unhealthy eating; 7) smoking; and, 8) drug addict, respectively. Their life assets derived from 5 powers of: 1) themself; 2) family; 3) school; 4) friend; and, 5) community, respectively. The projects achieved the goals and received continuously support from the community administrators because it served the needs of the community. The recommendation was that should to study factors causing the inappropriate behaviors of young adults for better develop the program. Keyword: Community, Inappropriate Health behavior, Life Cost, Young Adult